FUTURE INNOVATIVE TOOL POT (FITPOT) DAERAH GAMBUT SEBAGAI SOLUSI MENANAM SAYURAN DI DESA KUALU NENAS [FUTURE INNOVATIVE TOOL POT (FITPOT) FOR PEAT AREA AS A VEGETABLE PLANTING SOLUTION AT DESA KUALU NENAS] - Abrar Rifqi Pratama; Rizky Noviandri; Appriliya Destiyani; Marisya Wahyuna; Rezha Yaren; Monita Olivia (Jurnal Sinergitas PKM & CSR, 2019)
Kualu Nenas is a village in Kampar Regency with a distance about 27 km from the outskirt of Pekanbaru City, Riau Province. This village is located in peatland where a majority of people are farmers and traders. Pineapple is the primary commodity that is most dependable and very suitable in peat areas. Peat has low pH and acidic water that makes the soil cannot be planted for vegetables, so alternative farming or gardening system needs to be introduced to the community of Kualu Nenas. This condition becomes a reason for this community service activity to use Future Innovative Tool Pot (FITPOT) as an alternative gardening system in peatland. The FITPOT, a hydroponic gardening system, utilizing a peat water purification unit and hydroponic tools contains water as a medium for planting vegetables in the peat area. In this activity, the community service team presented information and training on how to build the FITPOT installation. Participants were very active and engaged in the training and started to seedling the plants after the training for the FITPOT. Results show the FITPOT is considered an alternative method to produce high-quality vegetables for the community consumption and potentially will provide a side income for people in Kualu Nenas village.Bahasa Indonesia Abstrak: Desa Kualu Nenas merupakan salah satu desa di Kabupaten Kampar berjarak sekitar 27 km dari pinggir Kota Pekanbaru, Provinsi Riau. Desa ini terletak di lahan gambut dengan mayoritas masyarakat berprofesi sebagai petani dan pedagang. Nenas menjadi komoditi utama yang paling diandalkan dan sangat cocok untuk ditanam di daerah gambut. Tanah gambut memiliki pH tanah dan air yang asam, hal itu menjadikan tanah gambut tidak dapat ditanami sayuran sehingga teknik berkebun alternatif perlu diperkenalkan kepada masyarakat desa Kualu Nenas. Kondisi tersebut melatarbelakangi kegiatan pengabdian masyarakat untuk Future Innovative Tool Pot (FITPOT) sebagai berkebun di lahan gambut. FITPOT, sistem berkebun hidroponik, menggunakan unit penjernihan air gambut dan perlengkapan hidroponik yang berisi air sebagai media menanam sayuran di lahan gambut. Pada kegiatan ini, tim pengabdian masyarakat memberikan informasi dan penyuluhan mengenai cara membuat instalasi FITPOT. Peserta sangat aktif dalam penyuluhan dan mulai menyemai sayuran setelah penyuluhan untuk FITPOT. Hasil kegiatan menunjukkan bahwa FITPOT merupakan metode alternatif untuk memperoleh sayuran berkualitas tinggi untuk konsumsi komunitas dan berpotensi memberikan pendapatan sampingan untuk masyarakat desa Kualu Nenas.